Advances in SXFA-Coated SAW Chemical Sensors for Organophosphorous Compound Detection - Yong Pan; Wen Wang; Shitang He; Shunzhou Li; Minghua Liu (Sensors, 2011)
A polymer-coated surface acoustic wave (SAW)-based chemical sensor for organophosphorous compound sensing at extremely low concentrations was developed, in which a dual-delay-line oscillator coated with fluoroalcoholpolysiloxane (SXFA) acted as the sensor element. Response mechanism analysis was performed on the SXFA-coated chemical sensor, resulting in the optimal design parameters. The shear modulus of the SXFA, which is the key parameter for theoretical simulation, was extracted experimentally. New designs were done on the SAW devices to decrease the insertion loss. Referring to the new phase modulation approach, superior short-term frequency stability (±2 Hz in seconds) was achieved from the SAW oscillator using the fabricated 300 MHz delay line as the feedback element. In the sensor experiment on dimethylmethylphosphonate (DMMP) detection, the fabricated SXFA-coated chemical sensor exhibited an excellent threshold detection limit up to 0.004 mg/m3 (0.7 ppb) and good sensitivity (~485 Hz/mg/m3 for a DMMP concentration of 2~14 mg/m3).